Long-lasting floods buffer the thermal regime of the Pampas - Houspanossian, Javier; Kuppel, Sylvain; Nosetto, Marcelo Daniel; Di Bella, Carlos Marcelo; Oricchio, Patricio; Barrucand, Mariana Graciela; Rusticucci, Matilde Monica; Jobbagy Gampel, Esteban Gabriel (Springer, 2018)
The presence of large water masses influences the thermal regime of nearby land shaping the local climate of coastal areas by the ocean or large continental lakes. Large surface water bodies have an ephemeral nature in the vast sedimentary plains of the Pampas (Argentina) where non-flooded periods alternate with flooding cycles covering up to one third of the landscape for several months. Based on temperature records from 17 sites located 1 to 700 km away from the Atlantic coast and MODIS land surface temperature data, we explore the effects of floods on diurnal and seasonal thermal ranges as well as temperature extremes. In non-flooded periods, there is a linear increase of mean diurnal thermal range (DTR) from the coast towards the interior of the region (DTR increasing from 10 to 16 K, 0.79 K/100 km, r 2 = 0.81). This relationship weakens during flood episodes when the DTR of flood-prone inland locations shows a decline of 2 to 4 K, depending on surface water coverage in the surrounding area. DTR even approaches typical coastal values 500 km away from the ocean in the most flooded location that we studied during the three flooding cycles recorded in the study period. Frosts-free periods, a key driver of the phenology of both natural and cultivated ecosystems, are extended by up to 55 days during floods, most likely as a result of enhanced ground heat storage across the landscape (~2.7 fold change in day-night heat transfer) combined with other effects on the surface energy balance such as greater night evaporation rates. The reduced thermal range and longer frost-free periods affect plant growth development and may offer an opportunity for longer crop growing periods, which may not only contribute to partially compensating for regional production losses caused by floods, but also open avenues for flood mitigation through higher plant evapotranspirative water losses.